Pengaruh latihan isometric handgrip terhadap tekanan darah penderita hipertensi pada lansia: Literature review - Agus Miraj Darajat; Rulla Luqiana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Hypertension is a non-communicable disease, which occurs in systolic blood pressure of 140 mmHg and diastolic 90 mmHg. The Elderly is one of the factors of hypertension. Prevalence of Hypertension according to Riskesdas 2018, Hypertension occurs in the age group of 31-44 years (31.6%), age 45-54 years (45.3%), and age 55-64 years (55.2%). Physical activity that can be used to lower blood pressure is the Isometric Handgrip Exercise which is done with static exercises on contracting muscles, without any change in muscle length or hand joint movement.Purpose: Analyzing research articles related to the effect of isometric handgrip exercise on blood pressure in patients with hypertension in the elderly.Method: A literature Review method using a systematic design with a research sample of 11 journals consisting of 2 national journals and 9 international journals indexed by ISSN and DOI, the sample collection technique is using purposive sampling with inclusion and exclusion criteria in it, feasibility evaluation data using the JBI Critical Appraisal Checklist for Analytical Quasy Experimental.Results: Based on the evaluation of the feasibility of scoring, 9 international journals, and 2 national journals were included in category A (strong recommendation).Conclusion: Shows that there is an effect of isometric handgrip exercise on blood pressure in patients with hypertension in the elderly.Suggestion: The results of this Literature Review are expected to be the basis for providing complementary interventions for hypertension drugs in community settings and also for the development of further research.Keywords: Isometric Handgrip; Hypertension; Elderly. Pendahuluan: Hipertensi merupakan penyakit tidak menular, yang terjadi pada tekanan darah sistolik ≥140 mmHg dan diastolik ≥90 mmHg. Lansia merupakan salah satu faktor terjadinya Hipertensi. Prevalensi Hipertensi menurut Riskesdas 2018, Hipertensi terjadi pada kelompok usia 31-44 tahun (31,6%), usia 45-54 tahun (45,3%), usia 55-64 tahun (55,2%). Aktivitas fisik yang dapat digunakan untuk menurunkan tekanan darah adalah Latihan Isometric Handgrip yang dilakukan dengan latihan statis pada otot yang berkontraksi, tanpa adanya perubahan pada panjang otot atau pergerakan sendi tangan.Tujuan: Menganalisis artikel penelitian terkait latihan isometric handgrip terhadap tekanan darah penderita hipertensi pada lansia.Metode: Penelitian Literature Review dengan menggunakan desain Systematic dengan sampel penelitian berjumlah 11 jurnal yang terdiri dari 2 jurnal Nasional dan 9 jurnal Internasional yang terindeks ISSN dan DOI, tekhnik pengumpulan sampel yaitu menggunakan purposive sampling dengan kriteria inklusi dan ekslusi didalamnya, evaluasi kelayakan data menggunakan JBI Critical Appraisal Checklist for Analitycal Quasy Experimental.Hasil: Berdasarkan dari evaluasi kelayakan scoring didapatkan 9 jurnal Internasional dan 2 artikel Nasional yang termasuk dalam kategori A (rekomendasi kuat).Simpulan: Analisa hasil penelitian literature review ini menunjukan ada pengaruh latihan isometric handgrip terhadap tekanan darah penderita hipertensi pada lansia.Saran: Hasil Literature Review ini diharapkan dapat menjadi dasar dalam memberikan intervensi pendamping obat hipertensi di tatanan komunitas dan juga pengembangan penelitian lanjutan.